2020
DOI: 10.7554/elife.55124
|View full text |Cite
|
Sign up to set email alerts
|

Hox-dependent coordination of mouse cardiac progenitor cell patterning and differentiation

Abstract: Perturbation of addition of second heart field (SHF) cardiac progenitor cells to the poles of the heart tube results in congenital heart defects (CHD). The transcriptional programs and upstream regulatory events operating in different subpopulations of the SHF remain unclear. Here, we profile the transcriptome and chromatin accessibility of anterior and posterior SHF sub-populations at genome-wide levels and demonstrate that Hoxb1 negatively regulates differentiation in the posterior SHF. Spatial mis-expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 90 publications
(160 reference statements)
4
57
0
Order By: Relevance
“…Initial studies on the contribution of the SHF to the developing heart mainly focused on its importance for the expansion of the arterial pole, showing that the anterior SHF (aSHF) primarily contributes to the outflow tract, right ventricle, and ventricular septum [ 9 , 12 , 13 ]. Subsequent studies demonstrated that the posterior SHF (pSHF) plays a role in the development of the venous pole by contributing to the DMP and its derivatives [ 4 , 14 ], the pAS [ 15 ], and to the atrial myocardium ( Figure 1 ), although the extent to which the pSHF contributes to the atrial myocardial tissues is still a matter of debate [ 16 ].…”
Section: Early Heart Developmentmentioning
confidence: 99%
“…Initial studies on the contribution of the SHF to the developing heart mainly focused on its importance for the expansion of the arterial pole, showing that the anterior SHF (aSHF) primarily contributes to the outflow tract, right ventricle, and ventricular septum [ 9 , 12 , 13 ]. Subsequent studies demonstrated that the posterior SHF (pSHF) plays a role in the development of the venous pole by contributing to the DMP and its derivatives [ 4 , 14 ], the pAS [ 15 ], and to the atrial myocardium ( Figure 1 ), although the extent to which the pSHF contributes to the atrial myocardial tissues is still a matter of debate [ 16 ].…”
Section: Early Heart Developmentmentioning
confidence: 99%
“…Perturbation of the SHF during elongation of the forming heart results in a spectrum of OFT defects associated with early embryonic lethality [ 11 , 12 , 13 ]. Lineage tracing analysis in mice has revealed that the SHF is sub-divided into distinct anterior and posterior regions (aSHF and pSHF) [ 14 , 15 ] ( Figure 1 ). Indeed, aSHF progenitors engender the right ventricular and proximal OFT myocardium, while progenitor cells located in the pSHF contribute to the formation of the atrial and atrioventricular septation through development of the dorsal mesenchymal protrusion (DMP) that forms the muscular base of the primary atrial septum [ 16 ].…”
Section: Embryonic Origins Of the Oftmentioning
confidence: 99%
“…Hoxb1 plays a key role in patterning those cardiac progenitor cells that contribute to both cardiac poles [ 15 ]. Progenitor cells expressing Hoxb1 alone or concomitantly with Hoxa1 contribute to the proximal dorsal OFT or distal OFT, respectively ( Figure 1 ).…”
Section: Hox Transcription Factorsmentioning
confidence: 99%
“…1e). Clusters C1 and C18 contains pSHF populations as identified by expression of Hoxb1 5 , Tbx5, Foxf1, and Wnt2 25,26 (Fig. 1f and Extended Data Fig.…”
Section: Identification Of Common Progenitor Cells In the Cpmmentioning
confidence: 99%
“…The pharyngeal apparatus consists of individual bulges of cells termed arches that form in a rostral to caudal manner from mouse embryonic days (E)8-10. 5. The cellular and molecular mechanisms of how CPM cells in the pharyngeal apparatus both are maintained in a progenitor state and are allocated to form the heart and BrMs in mammals, are unknown.…”
Section: Introductionmentioning
confidence: 99%